Evaluation of cross-section data for radionuclides used in positron emission tomography by effects of level density models using EMPIRE 3.2.2 code - Glara Fuad Hasan; Edrees Muhammad-Tahir Nury; Flavia Groppi (Ядерна фізика та енергетика)
This work presents the evaluated results of cross-sections for natural chromium (natCr) with several nuclear reactions of natCr(d,x)52g,m+Mn, natCr(d,x)54Mn, natCr(d,x)51Cr, and natCr(d,x)48V using the statistical nuclear model EMPIRE 3.2.2 code with different level density models, for some radionuclides used in positron emission tomography. We compared the results to data sets found in literature, and data chosen from various sets of the electronic TENDL library.